Teenagers and Social Media: The Influence of Multimedia on Online Interactions - Putri Suciyati; Nurul Hakiki; M. Hasan Amir Husen (Secure And Knowledge-Intelligent Research in Cybersecurity And Multimedia (SAKIRA), 2025)
In this era of globalization marked by rapid technological advances, the presence of social media has brought significant changes to the lives of teenagers. Social media is not only a means to interact with others, but also shapes the identity and behavior of teenagers. This study aims to explore the influence of social media on adolescent behavior and understand how social media affects the process of finding adolescent identity. Using a qualitative research approach, this study seeks to gain a deeper understanding of the phenomenon of the influence of social media on adolescents and its implications for their behavior and social interactions. The results of this study contribute to a broader understanding of the role of social media in the lives of adolescents and its impact on their development. This study also aims to provide recommendations for parents, educators, and policymakers to understand and address the impact of social media on adolescents. By doing so, this study can help raise awareness and understanding of the importance of managing healthy and positive social media use for adolescents. Furthermore, this study will examine the potential risks and benefits of social media use among adolescents, including its impact on mental health, social relationships, and academic performance. The findings of this study will provide valuable insights for stakeholders to develop effective strategies to promote healthy social media use among adolescents.